Respuesta :
Start by breaking the polynomial into two binomials:
x^2 + 4x - 12 = 0
(x+6)(x-2)=0
Now set each binomial equal to zero:
(x+6)=0
x=-6
(x-2)=0
x=2
So your answers are x=2 and x= -6
x^2 + 4x - 12 = 0
(x+6)(x-2)=0
Now set each binomial equal to zero:
(x+6)=0
x=-6
(x-2)=0
x=2
So your answers are x=2 and x= -6
Answer:
x = 2 or x = -6
Step-by-step explanation:
Here the given equation is,
[tex]x^2 + 4x - 12 = 0[/tex]
By middle term spitting,
[tex]x^2+(6-2)x-12=0[/tex]
[tex]x^2+6x-2x-12=0[/tex]
[tex]x(x+6)-2(x+6)=0[/tex]
[tex](x-2)(x+6)=0[/tex]
By Zero product property,
[tex]x-2=0\text{ or }x + 6 = 0[/tex]
[tex]\implies x = 2\text{ or } x = -6[/tex]
Which is the solution of the given equation.
Third option is correct.